Computed tomography‐guided intraluminal brachytherapy in recurrent bronchogenic carcinoma: A clinical trial in a small group. Issue Volume 1:Issues 2(2017) (6th July 2017) - Ma, Chenying; Xu, Xiaoting; Zhang, Ruting; Qin, Songbing; Zhou, Juying
Abstract: Objective: The overall survival (OS) of lung cancer patients has been significantly extended as a consequence of chemotherapy and targeted drug utilization, which has resulted in an increase in local recurrences. The present study followed patients to evaluate the short‐term and long‐term efficacies and the safety of high‐dose rate intraluminal brachytherapy (ILBT) in recurrent bronchogenic carcinoma patients, and investigate the factors that influence prognosis. Methods: The clinical records, treatment, curable effects, and adverse events of 15 patients treated in the First Affiliated Hospital of Soochow University, Suzhou, China, who were diagnosed with recurrent bronchogenic cancer between 1 June 2009 and 30 September 2015 were reviewed, and survival analysis was assessed by the Kaplan–Meier method. Results: A total of 15 recurrent bronchogenic carcinoma patients received ILBT, and information on curable effects and safety was available. The group consisted of two complete response (2/15), 11 partial response (11/15), one stable disease (1/15) and one progression disease (1/15). The response rate was 86.7% (13/15), and disease control (complete response + partial response + stable disease) was 93.3% (14/15). The dyspnea indexes of the patients decreased significantly in weeks 1, 2, 4, and 8 after ILBT treatment ( P  < 0.001). The average post‐ILBT partial remission period was 5.27 ± 3.35 months, and the median partial remission period was 3.24 months. The combination therapy of ILBT and bronchofiberscope ( P  = 0.013), and a total ILBT dose of ≥20 Gy could produce a partial effective rate. The progress‐free survival of patients was 9.5 months (95% CI 12.2–16.5 months), average progress‐free survival was 15.8 ± 14.4 months, median OS was 32.0 months (95% CI 25.0–30.0 months), 1‐year OS was 93.3% (14/15), and 3‐year OS was 40.0% (6/15). The main adverse events were bronchospasm and hemoptysis (grade III); others were grade I–II. Conclusion: Computed tomography‐guided ILBT is a safe, effective palliative treatment for recurrent bronchogenic carcinoma, but it requires further study in larger groups.